Pengaruh Suhu dan Lama Penyimpanan Daun Stephania hernandifolia Walp. terhadap Kualitas Bahan Baku Cincau dan Penerimaan Konsumen - Roiyana, Munirotun; Prihastanti, Erma; Kasiyati, Kasiyati (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Cincau is one of the gel-formed foods which is obtained from squeezing of certain leaves in the water. One of the plants that can be made to cincau is Stephania hernandifolia Walp. The obstacle faced in the making of cincau is the availability of cincau plant. At now days, it is difficult to get the cincau plant and also the handling of this plant has to be done carefully. Post-harvesting technique to keep the quality of cincau’s raw material is by storing at low temperature. Storing at low temperature can lengthen the storage time of the plant and maintain its fresh condition.  The aim of this research was to study the effect of storing the leaves at different temperature and time towards the percentage of yellowing area, vitamin C content and chlorophyll content of Stephania hernandifolia Walp. leaves, and also to determine the characteristics of cincau’s organoleptics. The research was done at Laboratory of Biology Structure and Function of Plant, Biology Department – Faculty of Mathematics and natural sciences, Diponegoro University in 2010. Complete Random Design with 3 x 2 factorial and three times repetition was used in this research. The first factor is time of storage which consists of 1, 3 and 5 days. The second factor is temperature of storing which consists of 14ºC and 28ºC. The data obtained was analysed with ANOVA, if there was difference then further test was done with Duncan test with 95% level of significance. Result showed that interaction between temperature and storage time affected the area of leaves yellowing and vitamin C content. The higher the temperature and the longer storage time widened the yellowing of the leaves. The chlorophyll content only affected by the time of storage. The organoleptics results indicated that the panelists prefered the cincau which was kept at 14ºC for 3 days. Key Word : Stephania hernandifolia Walp., yellowing area, chlorophyll , vitamin C, organoleptics.